"The Magic of Science:" Beyond Action, a Case Study on Learning Through Socioenaction - Duarte, Emanuel Felipe; Maike, Vanessa; Mendoza, Yusseli Lizeth Méndez; Brennand, Camilla; Baranauskas, M. Cecília (Anais do Workshop de Informática na Escola (WIE); 2019: Anais do XXV Workshop de Informática na EscolaDO - 10.5753/cbie.wie.2019.501, 2019)
Recent advances in Human-Computer Interaction (HCI) can significantly affect technology-enhanced educational contexts. Our evolving relationship technology is a challenging topic of investigation, but alternative theories to cognition and socially aware empirical studies can shed light on the subject. In this paper, we explore "The Magic of Science" workshop, conducted in an educational museum context. With a background on learning through action and enactivism, our objective is to observe how people can individually and socially experience pervasive digital technology in educational contexts. Our study included 15 participant children and adolescents, who explored an exhibit of three interactive artworks and then built an interactive artifact from scratch during the workshop. We observed how these interactions took place and collected feedback on the experience of the workshop. Our results indicate that new ways of interacting with pervasive technologies allow us to expand the concept of learning through action, towards learning through socioenaction.